Covalent organic frameworks with triazine units for iodine capture via weak molecular interactions. (31st March 2023) - Niu, Qianyuan; Cui, Qingxue; Meng, Xutong; Zhang, Pei; Zhou, Yining; Fu, Hao; Ma, Baiwei; Qin, Na; Zhai, Lipeng
Abstract : Triazine unit functionalized covalent organic frameworks were predesigned for exceptional iodine capture through weak molecular interactions. Abstract : Radioactive iodine in nuclear waste has become an unignorable problem of environmental pollution. In this work, two covalent organic frameworks (T-COF-1 and T-COF-2) with triazine units were synthesized for exceptional iodine capture via weak molecular interactions. Besides, the iodine capture capacity can be tuned via the design of building units, where the nitrogen content can be modified at the molecular level. Interestingly, T-COF-2 with higher triazine unit content affords a higher iodine uptake value.